On the origin of the German East-West population gap - Christoph Eder; Martin Halla (Johannes Kepler University of Linz, Department of Economics, 2018)
The East-West gap in the German population is believed to originate from migrants escaping the socialist regime in the German Democratic Republic (GDR). We use newly collected regional data and the combination of a regression discontinuity design in space with a difference-in-differences approach to document that the largest part of this gap is due to a massive internal migration wave 3 years prior to the establishment of the GDR. The timing and spatial pattern of this migration movement suggest that the dominant motive was escaping physical assault by the Soviet army and not avoiding the socialist regime. The gap in population has remained remarkably sharp in space and is growing.
Keywords: N44; N94; R23; R11; R12; J61; 330; Institutions; wartime violence against civilians; regional migration; WorldWar II; Germany; spatial distribution; regional economic activity